Attitudes of Patients with Adrenoleukodystrophy towards Sex-Specific Newborn Screening - Hemmo A. F. Yska; Lidewij Henneman; Rinse W. Barendsen; Marc Engelen; Stephan Kemp (MDPI AG, 2023)
Newborn screening (NBS) for X-linked adrenoleukodystrophy (ALD) can identify affected individuals before the onset of life-threatening manifestations. Some countries have decided to only screen boys (sex-specific screening). This study investigates the attitudes of individuals with ALD towards sex-specific NBS for ALD. A questionnaire was sent to all patients in the Dutch ALD cohort. Invitees were asked who they thought should be screened for ALD: only boys, both boys and girls or neither. The motives and background characteristics of respondents were compared between screening preferences. Out of 108 invitees, 66 participants (61%), 38 men and 28 women, participated in this study. The majority (n = 53, 80%) favored screening both newborn boys and girls for ALD, while 20% preferred boys only. None of the respondents felt that newborns should not be screened for ALD. There were no differences in the background characteristics of the respondents between screening preferences. Our study revealed a diverse range of motivations underlying respondents' screening preferences. This study is one of the first to investigate the attitudes of patients towards sex-specific screening for ALD. The outcomes of this study can offer insights to stakeholders engaged in the implementation of NBS programs. ALD patients are important stakeholders who can provide valuable input in this process.